PERANCANGAN SISTEM PEMBELAJARAN LMS MATAKULIAH BAHASA INDONESIA: PERANCANGAN SISTEM PEMBELAJARAN LMS MATAKULIAH BAHASA INDONESIA - heri nuryanto; Eryd Saputra; Eva Amalia; Hendra Syaiful; Annisa Ulhasanah (Computer Based Information System Journal, 2025)
The flexibility of the concept of education is slowly shifting from face-to-face learning, which means that the presence of educators and students is the main indicator in the teaching and learning process in the classroom to a distance education system. Learning Management System (LMS) is a web-based software program that is widely used for management activities, documentation, monitoring, reporting, administration and distribution of educational content, training programs, technical manuals, instructional videos, digital libraries, and learning projects. The objectives of this study are: 1) To find out how the workflow of the Indonesian language course learning system works; 2) To determine the model and function of the system in detail; and 3) To find out the data flow through a visual approach. The research method used to complete this research is the iterative and agile systems development lifecycle method. from the results of the study it can be seen that there are 3 entities that play a role in the process of this system, namely: Admin, Lecturer, and Student